Efficacy of Pyroxasulfone against Weeds and their Impact on Yield and Economic Analysis of Wheat - Bhalse, Lakhan; Jha, A. K.; Verma, Badal; Dubey, Abhijeet; Surendra (International Journal of Economic Plants, 2024)
A field experiment was conducted during the rabi season (November, 2021–April, 2022) at AICRP on Wheat, College of Agriculture, Jawaharlal Nehru Krishi Vishwa Vidyalaya, Jabalpur, Madhya Pradesh, India to evaluate the efficacy of Pyroxasulfone in wheat cultivation to enhance crop productivity and profitability. The study assessed eight weed management treatments, including herbicide applications (pendimethalin at 1000 g ha-1; pyroxasulfone at 127.5 g ha-1; pendimethalin+pyroxasulfone at 1250+127.5 g ha-1; metribuzin at 300 g ha-1; pendimethalin+metribuzin at 1250+280 g ha-1; pyroxasulfone+metribuzin at 127.5+280 g ha-1 as pre-emergence), hand weeding once at 25 DAS and weedy check, in a randomized block design with three replications. The experimental field was dominated by Phalaris minor (17.82%) among monocot weeds, while Medicago denticulata (28.97%), Cichorium intybus (26.19%), Chenopodium album (16.10%), and Anagallis arvensis (10.92%) among the dicot weeds throughout the crop growing period. Results revealed a substantial decrease in weed density and dry weight across all treatments, with the combination of pyroxasulfone+metribuzin at 127.5+280 g ha-1 showing superior efficacy. Weed control efficiency was highest with hand weeding, followed by herbicide treatments. Additionally, treatments significantly influenced wheat growth parameters and yield attributes, with the application of pyroxasulfone+metribuzin at 127.5+280 g ha-1 resulting in the tallest plants and highest number of tillers square-1 meter. Grain yield was also found significantly higher in plots treated with pyroxasulfone+metribuzin at 127.5+280 g ha-1. The economic analysis demonstrated that pyroxasulfone+metribuzin at 127.5+280 g ha-1 yielded the highest net monetary returns, indicating its economic viability.